Listening for Safe Places: Networks of Playing and Chalcedon in Disaster Pastoral Care. Issue 4 (4th December 2017) - Johannessen‐Henry, Christine Tind
Abstract: Disaster pastoral care operates in diverse contexts, which may challenge clergy responders in ecclesiological meaning‐making of their practices of care. This article argues that pastoral care may be imagined as part of a larger "network" of caring acts understood as a collective, multiple care practice. Such practice reflects deep‐rooted movements described in psychoanalytical theory as playing, and the christological idea of communication of properties . Therein, spiritual "safe places" can be seen to emerge, even in the midst of traumatic events.